Histomorphologic liver abnormalities in a group of alcoholic patients - Libán Álvarez Cáceres; Marcos Félix Osorio Pagola; Merlyn Arce Núñez. (Medisur)
Background: the ingestion of alcohol has been directly involved in the development of liver diseases. Nowadays, the liver damage by ethanol is a serious health problem all over the world. To achieve satisfactory results In order to face it, it is necessary to provide multidisciplinary attention. Objective: to determine the histomorphologic liver impairments in alcoholic patients. Methods: an observational, descriptive, co-relational and prospective study conducted in 23 patients with an alcoholism diagnosis at the Provincial University Hospital "Arnaldo Milián Castro" in Villa Clara. Inclusion and exclusion criteria were taken into account. The variables studied were: laparoscopic evolution, period of time consuming alcohol (in years), histologic evolution and alanine aminotransferase. Results: both trough laparoscopic and liver biopsy, the most frequent diagnosis was steatosis, followed by chronic hepatitis. In one patient cirrhosis was diagnosed through laparoscopy: a biopsy was not performed in this case. Conclusion: there were a high proportion of patients with impaired liver aminotransferases and severe histological diagnoses, especially those of chronic hepatitis and liver cirrhosis.